Analysis of Michael Riffaterre's Semiotics in the Poem “Syaiun Sayabqa Bainana” by Faruq Juwaidah - Al Abid, Misbahul Munir; Roziki, Khafid (Journal of Language and Literature Studies, 2025)
Poetry is different from other genres of literature, such as prose and drama. The difference lies in the language used in poetry, which is usually multi-interpretive, metaphorical, and ambiguous. This ambiguity of poetry creates different interpretations, if read and perceived by different readers. Therefore, this study aims to describe Michael Riffaterre’s semiotics to the poem “Syaiun Sayabqa Bainana” by Faruq Juwaidah. This research methode is descriptive qualitative which the data and studies are based on various sources, then analyzed using Riffaterre’s theory by looking at the indirecyness of xcpressions, reading heuristic and hermeneutic, models, variants, matrices, and hypogram, which revealed that the holistic meaning of this poem. The research findings show that the poem Syaiun Sayabqa Bainana means longing, namely longing for the tranquility of life in a world full of sadness and suffering. Then through models and variants in the form of words, phrases, and sentences, the matrix is found to be the search for tranquility, through doubts and beliefs and a world full of suffering and materialism, although in the end everything is ephemeral. The potential hypogram of this poem is Faruq Juwaidah's criticism of the social and political upheaval in Egypt. And the actual hypogram is the poem “Ila Habibti” by Nizar Qabbani.